SOCIO-HISTORICAL ESSENCE OF THE EDUCATIONAL SYSTEM - Iskandarova Dildora Mannapjonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
this article describes the development of educational tourism in Uzbekistan and the high results achieved, as well as analytical conclusions about the reforms that are still required to be carried out, their future effect, as well as the increasing democratization and liberalization of society and the extent to which the educational system and students also affect their activities, what requirements the employer.